(untitled) (Journal of Applied Membrane Science & Technology, 2022)
Emulsion liquid membrane (ELM) has been widely studied as an alternative method for amine absorption technology in the removal of acid gases such as carbon dioxide (CO2) and hydrogen sulphide (H2S). However, searching for stable ELM formulation with an enhanced CO2 absorption remains as challenge. Therefore, in this study, the aqueous solution containing a mixture of methyl diethanolamine (MDEA) and 2-amino-2-methyl-1-propanol (AMP) in sodium hydroxide (NaOH) solution was introduced as a dispersed phase, kerosene as continuous phase and Span-80 acts as a surfactant for the formation of water-in-oil (W/O) emulsion. In this study, the dispersed phase consists of 8% v/v MDEA and 4% v/v AMP and the continuous phase which contains 6% v/v Span-80 produced a stable emulsion and exhibited 65.2% of CO2 removal. This study indicates that the introduction of blended amine able to produce stable emulsion with an enhanced CO2 removal.